A Bioengenharia como ferramenta para restauração ambiental das margens do Rio São Francisco - Gomes, Luciana Godinho Nery (2005)
Since the 70s, the lower São Francisco river basin, in the border of Sergipe and Alagoas States (Northeast/Brazil), has been submitted to strong environmental impacts that changed in the hydrological and sedimentological regimen as a result of dam s construction and degradation of the riparian vegetation. Bank erosion has caused enlargement and sedimentation of the channel (margin withdraw). The objective of this work was to evaluate the bank erosion control in a river margin site through the use of bioengineering to stabilize the river bank and the restoration of the riparian vegetation. Biotextile Fibrax® 400 BF associated to Brachiaria decumbens grass, trees and a line of bermalongas in the river water line were used. The tree species of Caesalpinia leiostachya, Cassia grandis, Enterolobium contortisiliquum, Erythrina velutina, Schinus terebinthifolia and Tapirira guianensis were evaluated by seedling development, relative growth rate of the height in the plant dossel and crown diameter. The river bank morphological changes were monitored by transverse topographic profiles in some parts of the river bank with and without bioengineering technique. After seven months, the efficiency of the biotêxtil controlling bank erosion was measured. Regarding to the development of plant species, besides Erythrina velutina, there was a better development in the experimental area without the biotextile. Related to plant height and crown there was a better development of the Enterolobium contortisiliquum and Caesalpinia leiostachya species. It was also observed that and the Erythrina velutina was the only species to show a better development in the area with in comparison to the area without biotextile, and the Cassia grandis did not reach a significant development, according with all measured parameters. A strong and destructive bank erosion process was observed in the site without bioengineering technique application.